Themes of Alienation and Disillusionment in Mohan Rakesh's?Adhe Adhure: A Literary Analysis - Krishnamurthy, Sugirtha (Journal of Educational Research and Policies, 2025)
Mohan Rakesh’s Adhe Adhure (translated as Halfway House) is a poignant exploration of human relationships, identity, and the psychological dissonance created by alienation and disillusionment. The play is a seminal work in modern Indian theatre, reflecting the existential struggles of the post-independence era. This paper aims to examine the central themes of alienation and disillusionment in Adhe Adhure, exploring how Rakesh portrays the complex psychological landscapes of his characters, their interpersonal dynamics, and the broader socio-cultural context. By analyzing the emotional and existential crises of the play’s protagonists, this paper argues that Rakesh uses these themes to critique societal norms and to expose the inherent contradictions in the quest for self-actualization and human connection.